STRATEGIC MANAGEMENT ANALYSIS OF STARBUCKS CEMPAKA PUTIH: DIFFERENTIATION STRATEGY IN INDONESIA'S COFFEE MARKET - Apap Pulaya; Dessya Natalia Rendi. S; Nadiyah; Pitna Sari; Mohamad Rizqi Ramadhani (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
The rapid growth of the coffee shop industry in Indonesia has intensified competition among premium and local coffee brands. This study analyzes the strategic management practices of Starbucks Cempaka Putih, located in Central Jakarta, focusing on how the outlet sustains competitive advantage in a competitive coffee market. A qualitative field research approach was employed, combining direct observation, semi-structured interviews with store management and customers, and document analysis. The qualitative method was selected to provide in-depth insights into customer behavior and managerial practices that cannot be fully captured through quantitative approaches. Analytical tools including Porter’s Five Forces, PESTEL, SWOT, IFE/EFE matrices, and TOWS analysis were applied. Although QSPM is a commonly used strategic tool, it was not utilized in this study due to its complexity and limited relevance to the scope of this research. The findings indicate that Starbucks Cempaka Putih successfully implements a differentiation strategy anchored in the “third place” concept and a strong digital loyalty ecosystem (Starbucks Rewards). The SWOT analysis identifies key internal and external factors, while the TOWS analysis translates these findings into actionable strategies, demonstrating a clear linkage between analysis results and strategic recommendations. The IFE score of 2.79 and EFE score of 2.93 indicate strong internal capability and external responsiveness. The store generates approximately IDR 11–12 million in daily revenue with a team of 7 employees. Based on urgency and impact considerations, several strategic recommendations are proposed to enhance competitiveness.